Islamic culture and globalisation: Challenges and responses - Ullah, Md Cholem (IIUC Studies, 2020)
This paper is a humble endeavor to look at the relationship between Islam and globalisation from cultural perspective. The paper explores the nature of Islamic culture and its interaction with the west as part of the fundamental factors of how the west employ the policies against Islam in the most inhumane form. Now, western powers have been propagating against Islam. It is thus significant to analyze the role of ummah in this milieu of cultural globalisation for preparedness in shaping and constructing the course of globalisation in the coming days. This paper seeks to explain how will ummah meet challenges facing Islam as a cultural participator in globalisation where Islam is attributed with terrorism and other allegations, albeit is not Islamic at all and will never been part of the Islamic teaching and culture.Against this backdrop, Islam's future and its culture depend on Muslim ummah’s ability and their uncompromising mindset- not to integrate modernity and western culture into Islam but to make the new global order that can infuse religious norms like solidarity, community and identity. IIUC Studies Vol.16, December 2019: 57-76